Host factor reveals the intrinsic enzymatic activity of a bacterial effector. (December 2008) - Auweter, Sigrid D; Bhavsar, Amit P; Finlay, B Brett
Evaluation of: Lossi NS, Rolhion N, Magee AI, Boyle C, Holden DW: The Salmonella SPI-2 effector SseJ exhibits eukaryotic activator-dependent phospholipase A and glycerophospholipid:cholesterol acyltransferase activity. Microbiology 154, 2680––2688 (2008). The integral role that pathogenic bacterial effectors play during infection is well accepted; however, the biochemical activities of many pathogenic bacterial effectors remain unknown. Complicating the matter is the interplay between the bacterial effector and the host-cell environment. By way of example Lossi et al. demonstrate that recombinant SseJ is catalytically inactive in vitro but can be activated by a eukaryotic proteinaceous factor that remains to be identified and characterized.